(3Jbhje GdUMIs
(3ChdgG (B:s
(3Jbhje GdUMI HGdCSHGH GdSJg GdJi dGHO dcd EfSGf jDKQ OhGe UMJg ef JYOjdgG hGSJYeGdgG s
(3BNQgG (B:s
(3Effi de CHb cJGHkG Ufa ajeG CfG HSHjdg EdG hbQCJg YfO JUfjai gPG EjKGQkG efi GdJbQH Edi bdhH SGOJi hENhGJi s
(3Cdag eUfag HWQjbI GdLOGhds
(3hYeO ajg Edi PcQ GdefGaY Ohf GdHQGgjf ddENJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs